2019
DOI: 10.1103/physrevb.100.161113
|View full text |Cite
|
Sign up to set email alerts
|

Helical magnetic ordering in Sr(Co1xNix)2As2

Abstract: SrCo2As2 is a peculiar itinerant magnetic system that does not order magnetically, but inelastic neutronscattering experiments observe the same stripe-type antiferromagnetic (AF) fluctuations found in many of the Fe-based superconductors along with evidence of magnetic frustration. Here we present results from neutron diffraction measurements on single crystals of Sr(Co1-xNix)(2)As-2 that show the development of long-range AF order with Ni doping. However, the AF order is not stripe type. Rather, the magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…We calculated the turn angle kd between adjacent ab-plane ordered moments along the helix c axis within MFT from the ratio χ ab (T → 0)/χ (T N ) for the crystals showing AFM ordering and found that the helix turn angle varies with Ni concentration. Magnetic neutron diffraction measurements from two groups [63,64] confirm the helical magnetic structure with turn angles of the same order as those estimated here.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We calculated the turn angle kd between adjacent ab-plane ordered moments along the helix c axis within MFT from the ratio χ ab (T → 0)/χ (T N ) for the crystals showing AFM ordering and found that the helix turn angle varies with Ni concentration. Magnetic neutron diffraction measurements from two groups [63,64] confirm the helical magnetic structure with turn angles of the same order as those estimated here.…”
Section: Discussionsupporting
confidence: 82%
“…The above MFT discussion of helical ordering may be expected to be of only qualitative significance, since the MFT was formulated for local-moment AFMs instead of itinerant AFMs. However, magnetic neutron diffraction measurements [63,64] found that the magnetic structure is indeed helical, with helix turn angles that decrease from 104 • to 94 • on increasing x from x = 0.06 to 0.15, which have the same trend and are of the same order as we infer in Fig. 12 from Eq.…”
Section: B Molecular-field-theory Analysis Of Magnetic Susceptibility In the Ordered State In Terms Of Helical Afm Orderingsupporting
confidence: 74%
“…Recently, non-Fermi-liquid types of behavior associated with a composition-induced magnetic quantum-critical point in Sr(Co 1−x Ni x ) 2 As 2 crystals near x = 0.3 has been reported [37]. In addition, crystals of Sr(Co 1−x Ni x ) 2 As 2 with 0 < x < 0.3 exhibit c-axis helical or spin-density-wave AFM ordering [37][38][39], which is quite unusual in itinerant antiferromagnets. A small amount (2.5%) of La doping has been reported to cause FM ordering in Sr 1−x La x Co 2 As 2 [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Additional scans along (00L), (10L), and ( 1 2 0L) at T = 4.8 and 20 K (not shown) do not show evidence of new emerging Bragg reflections that may indicate magnetic ordering that is different from A-type AFM ordering. For instance, the absence of magnetic reflections along (00L) eliminates the helical structure recently discovered in the related Sr(Co 1−x Ni x ) 2−y As 2 system in which adjacent FM layers (moments aligned in the plane) are rotated at a finite angle as they stack along the c axis [29]. We note that examination of nuclear Bragg reflections do not show increased intensity as the temperature is lowered from 20 K to base temperature thus excluding FM ordering of the whole system assuming that the ordered moment is not larger than ∼ 0.1 µ B .…”
Section: Neutron Diffractionmentioning
confidence: 99%
“…In contrast to 122-type iron-arsenide compounds, none of the parent cobalt arsenides exhibit superconductivity even with doping but are still found to be rich in physics associated with itinerant magnetism of the conduction electrons [14][15][16][17][18][19][20][21][22][23][24]. Interesting physical properties are observed including non-Fermi-liquid behavior associated with a quantum critical point, spin-glass behavior, and helical magnetic ordering in electron-or hole-doped 122-type CoAs-materials [25][26][27][28][29][30][31][32]. For example, metallic SrCo 2 As 2 is a Stoner-enhanced paramagnet and does not exhibit any magnetic ordering down to a temperature T of 0.05 K; however, stripe-type AFM fluctuations were revealed via inelastic neutron-scattering (INS) measurements [16][17][18].…”
Section: Introductionmentioning
confidence: 99%